2019
DOI: 10.1093/jme/tjz139
|View full text |Cite
|
Sign up to set email alerts
|

Excito-repellency Activity of Andrographis paniculata (Lamiales: Acanthaceae) Against Colonized Mosquitoes

Abstract: Excito-repellency activity of plant extracts have been increasingly studied as mosquito repellents. In this study, the crude extract of Andrographis paniculata was evaluated for its noncontact repellency, contact excitation (irritancy + repellency), and knockdown/toxicity response against five colonized mosquitoes; Aedes aegypti (L.), Aedes albopictus (Skuse), Anopheles dirus Peyton & Harrison, Anopheles epiroticus Linton & Harbach, and Culex quinquefasciatus Say (Diptera: Culicidae) using an excito-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The three primary modes of action of a chemical are insecticidal (killing) and two behavioral responses, either by contact locomotor excitation ('irritancy') and/or noncontact spatial repellency [26]. The excito-repellency (ER) assay system is a well-established behavioral testing system to evaluate sublethal chemical actions such as contact excitation and noncontact repellency of synthetic and natural-derived compounds [27][28][29][30][31][32][33][34][35][36]. By measuring flight movement, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The three primary modes of action of a chemical are insecticidal (killing) and two behavioral responses, either by contact locomotor excitation ('irritancy') and/or noncontact spatial repellency [26]. The excito-repellency (ER) assay system is a well-established behavioral testing system to evaluate sublethal chemical actions such as contact excitation and noncontact repellency of synthetic and natural-derived compounds [27][28][29][30][31][32][33][34][35][36]. By measuring flight movement, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti , even at the highest concentration (5.0% w/v = 50,000 ppm), when exposed to treated-filter paper inside the ER chamber. It has been previously suggested that mosquitoes can avoid collectively lethal doses at exposures of only 30 min or less (if they escaped) in a larger space within the ER chamber (33.5 × 22.5 × 22.5 cm) ( Sukkanon et al, 2020 ). One limitation of this study is that the ER chambers were made of window-less stainless steels; therefore, we were unable to observe and confirm mosquito movement inside each chamber during the exposure period.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus and Ae. aegypti at high concentrations (2.5%–5.0% w/v; Sukkanon et al, 2020 ). Contrarily, contact irritancy and non-contact repellency are the primary and secondary actions, respectively, of Cananga odorata oil and are mainly used against the night-biting mosquitoes An.…”
Section: Introductionmentioning
confidence: 99%
“…4 A) ( Kumar et al, 2019 ). Recent studies have reported numerous pharmacological properties of Herba andrographitis extracts, both in vitro and in vivo , against HIV (EC 50 value of 5.49 μg/mL) ( Feng et al, 2012 ), complement (EC 50 value of 23.1–638.3 μg/mL) ( Wen et al, 2020 ), and excito-repellency (96.7% escape at 0.5–5.0% w/v concentration) ( Sukkanon et al, 2019 ). This agent has also been used to treat osteoarthritis in the knee; a 300 mg/day dose was effective and safe when applied to reduce pain ( Hancke et al, 2019 ).…”
Section: Promising Chinese Herbal Medicine Monomer Preparations For Tmentioning
confidence: 99%